SIFAT PUTUSAN FINAL DAN MENGIKAT DEWAN KEHORMATAN PENYELENGGARA PEMILU - Sitompul, Kevin Reynara Parsaulian; Poltak Siringoringo; Edward ML Panjaitan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
DKPP through Decision Number: 317-PKE-DKPP/X/2019 dismissed Evi Novida Ginting Manik as a Member of KPU RI. President Joko Widodo then issued Presidential Decree No. 34/P of 2020 dismissing Evi Novida Ginting disrespectfully as of March 23, 2020. Evi Novida Ginting fought back by suing the Presidential Decree to the Jakarta State Administrative Court (PTUN). Jakarta PTUN Decision Number: 82/G/2020/PTUN-JKT "grants for all" of Evi's lawsuit. The purpose of the research is to find out how the status, authority and position of the DKPP according to the applicable laws and regulations and find out whether the DKPP has the authority to dismiss the KPU Commissioner through its ethical judicial mechanism and know the nature of the DKPP ruling and its legal relationship with the Presidential Decree. This research uses descriptive qualitative analysis methods with case study and normative juridical approaches as well as other types of descriptive analysis research. Data collection techniques use literature studies. Data analysis uses qualitative. The results showed that the final and binding DKPP decision does not include decisions issued by judicial bodies, but rather entered into decisions issued by state administrative bodies or officials. The position of the DKPP as a judicial quasi institution for election organizers is not under the power of the judiciary as the constitutional court decree No. 115 / PHPU. D-XI/2013.